Education on Prevention and Management of Gestational Diabetes of Pregnant Women at the Obstetrics and Gynecology Clinic of Rumah Sakit Kabupaten Kediri (RSKK) - Prima Dewi Kusumawati; Siti Komariyah; Binti Ratna Khomsiyatin (Journal of Community Service for Health, 2025)
Gestational Diabetes Mellitus (GDM) is glucose intolerance that first appears or is detected during pregnancy and can lead to various complications for both the mother and the fetus. Preventing and managing GDM can be achieved through nutrition and physical activity education. This education aimed to enhance the understanding of pregnant women so that they can adopt a healthy lifestyle to prevent GDM. This study employed an analytical approach with a cross-sectional design. The population consisted of pregnant women visiting the obstetrics and gynecology clinic. This community service activity was conducted at the Obstetrics and Gynecology Clinic of Kediri Regency Hospital (RSKK) using lecture-based counseling, interactive discussions, and the distribution of educational leaflets. Evaluation was done by comparing pregnant women's knowledge levels before and after counseling using a pre-test and post-test. Data were analyzed using the Wilcoxon statistical test. Among the 40 respondents who participated in the counseling before the education, it was found that 24 pregnant women (60%) had low knowledge levels, 12 pregnant women (30%) had moderate knowledge, and only 4 (10%) had good knowledge. After the counseling, a significant improvement was observed, with 35 pregnant women (88%) had good knowledge and five pregnant women (12%) had moderate knowledge. The Wilcoxon test results indicated a significant increase in knowledge after the educational intervention. This education program should be continuously implemented with the support of healthcare workers and adequate facilities to raise awareness and prevent the occurrence of GDM in pregnant women.